Rapid Identification of Pseudallescheria and Scedosporium Strains by Using Rolling Circle Amplification - Lackner, Michaela (American Society for Microbiology, 2012)
The Pseudallescheria boydii complex, comprising environmental pathogens with Scedosporium anamorphs, has recently been subdivided into five main species: Scedosporium dehoogii, S. aurantiacum, Pseudallescheria minutispora, P. apiosperma, and P. boydii, while the validity of some other taxa is being debated. Several Pseudallescheria and Scedosporium species are indicator organisms of pollution in soil and water. Scedosporium dehoogii in particular is enriched in soils contaminated by aliphatic hydrocarbons. In addition, the fungi may cause life-threatening infections involving the central nervous system in severely impaired patients. For screening purposes, rapid and economic tools for species recognition are needed. Our aim is to establish rolling circle amplification (RCA) as a screening tool for species-specific identification of Pseudallescheria and Scedosporium. With this aim, a set of padlock probes was designed on the basis of the internal transcribed spacer (ITS) region, differing by up to 13 fixed mutations. Padlock probes were unique as judged from sequence comparison by BLAST search in GenBank and in dedicated research databases at CBS (Centraalbureau voor Schimmelcultures Fungal Biodiversity Centre). RCA was applied as an in vitro tool, tested with pure DNA amplified from cultures. The species-specific padlock probes designed in this study yielded 100% specificity. The method presented here was found to be an attractive alternative to identification by restriction fragment length polymorphism (RFLP) or sequencing. The rapidity (<1 day), specificity, and low costs make RCA a promising screening tool for environmentally and clinically relevant fungi.